Intelligent temperature-control self-repairing aluminum-based composite material and preparation method thereof

By combining the shape memory alloy microfilament and microcapsule repair system with aluminum-based composite materials, the problems of fatigue damage and performance degradation in traditional aluminum alloy materials during long-term service are solved, and intelligent temperature-controlled self-repair and multiple repair capabilities are achieved, which significantly improves the service life and mechanical properties of the material.

CN119614957APending Publication Date: 2025-03-14NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411801492.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Traditional aluminum alloy materials are prone to fatigue damage and performance degradation during long-term service. Existing self-repair materials have problems such as external stimulation dependence, limited repair times, and challenges in interface combination and mechanical performance balance.

Method used

By combining the shape memory alloy microfilament and microcapsule repair system with aluminum-based composite materials, a new material with intelligent temperature control and self-repair capability is realized. The material realizes the collaborative integration of multiple functions at the molecular and micro level, with intelligent response, multiple self-repair and excellent mechanical properties.

Benefits of technology

It realizes intelligent temperature control self-repair of the material, significantly improves the multiple repair capabilities, and overall improves the mechanical performance, extends the service life of the material, reduces maintenance costs, and improves the reliability and safety of the system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005178148080000141
    Figure BDA0005178148080000141
  • Figure BDA0005178148080000142
    Figure BDA0005178148080000142
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum-based composite materials, in particular to an intelligent temperature control self-repairing aluminum-based composite material and a preparation method of the intelligent temperature control self-repairing aluminum-based composite material. 5-15 parts of shape memory alloy microwires; 4.3 to 11.8 parts of epoxy resin prepreg containing microcapsules; wherein the epoxy resin prepreg containing microcapsules is composed of the following components: 3-8 parts of epoxy resin; 0.3 to 0.8 part of a curing agent; according to the invention, the advantages of a metal material, a composite material and an intelligent material are ingeniously combined. The aluminum alloy matrix provides excellent specific strength and specific stiffness, the shape memory alloy microwires endow the material with intelligent response capability, and the microcapsule system realizes a chemical repair function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum-based composite materials, and in particular to an intelligent temperature-controlled self-repairing aluminum-based composite material and a preparation method thereof. Background Art

[0002] In the modern industrial field, especially in aerospace and advanced manufacturing, the requirements for material performance are becoming increasingly stringent. Although traditional aluminum alloy materials are widely used for their light weight and high strength, they face the challenges of fatigue damage and performance degradation during long-term service. This not only affects the service life of components, but also increases maintenance costs and safety risks. In response to this problem, the concept of self-healing materials came into being and became a research hotspot in the field of materials science.

[0003] In recent years, the technology of self-healing materials has made significant progress. Researchers have developed a variety of self-healing strategies, such as microcapsule technology, hollow fiber systems, etc. These methods have improved the service life and reliability of materials to a certain extent. However, existing self-healing materials still have many limitations. First, most self-healing processes require external stimulation, such as heating or applying pressure, which is often difficult to achieve in practical applications. Secondly, traditional self-healing materials can usually only be repaired a limited number of times and cannot meet the needs of long-term service. In addition, combining self-healing functions with high-performance structural materials (such as aluminum alloys) also faces challenges such as interface bonding and balance of mechanical properties.

[0004] In view of this, it is particularly urgent to develop new materials that can intelligently respond to environmental changes, have multiple self-repair capabilities, and maintain excellent mechanical properties. Such materials can not only significantly extend the service life of components, but also significantly reduce maintenance costs and improve the reliability and safety of the system. Summary of the invention

[0005] The present invention proposes an innovative solution to the shortcomings of the existing technology. By cleverly combining shape memory alloy microwires, microcapsule repair systems and aluminum-based composite materials, a new material with intelligent temperature control and self-repairing capabilities is realized. This material realizes the synergistic integration of multiple functions at the molecular and microscopic levels, showing unique technical advantages.

[0006] The object of the present invention is to provide a thermally intelligent temperature-controlled self-repairing aluminum-based composite material, the material comprising the following components in parts by weight:

[0007] Aluminum alloy matrix 80-90 parts;

[0008] 5-15 parts of shape memory alloy microwires;

[0009] 4.3-11.8 parts of epoxy resin prepreg containing microcapsules;

[0010] Wherein, the epoxy resin prepreg containing microcapsules is composed of the following components:

[0011] Epoxy resin 3-8 parts;

[0012] Curing agent 0.3-0.8 parts;

[0013] 1-3 parts of microcapsules.

[0014] Preferably, the aluminum alloy matrix is ​​6061-T6 aluminum alloy.

[0015] Preferably, the shape memory alloy microwire is nickel-titanium alloy, and its diameter is 50-100 μm.

[0016] Preferably, the epoxy resin is bisphenol A epoxy resin (DGEBA), and the curing agent is 4,4'-diaminodiphenylmethane (DDM).

[0017] Preferably, the shell material of the microcapsule is polyurea formaldehyde, and the core material is dicyclopentadiene (DCPD).

[0018] The method for preparing the intelligent temperature-controlled self-repairing aluminum-based composite material comprises the following steps:

[0019] (1) preparing microcapsules;

[0020] (2) preparing epoxy resin prepreg containing microcapsules;

[0021] (3) preparing composite materials by vacuum pressure infusion casting;

[0022] (4) Heat treating the obtained composite material.

[0023] Preferably, the method for preparing microcapsules in step (1) comprises:

[0024] First, add deionized water, polyvinyl alcohol and sodium dodecylbenzene sulfonate into a three-necked flask, heat to 40±2℃ and stir to dissolve;

[0025] Secondly, a mixture of dicyclopentadiene and Grubbs first generation catalyst is added to the above solution for emulsification;

[0026] Then, urea and ammonium chloride were added, and formaldehyde solution was added dropwise;

[0027] Again, the temperature was raised to 55 ± 2 °C and maintained for 4 hours;

[0028] Finally, it was cooled, filtered, washed, and vacuum dried at 40±2°C for 24 hours.

[0029] Preferably, the method for preparing the epoxy resin prepreg containing microcapsules in step (2) comprises:

[0030] First, the epoxy resin and curing agent were stirred and mixed at 60±2℃;

[0031] Secondly, add microcapsules and stir gently at 40±2℃;

[0032] Then, the mixture was applied to a fiberglass cloth;

[0033] Finally, vacuum drying was performed at room temperature for 12 h.

[0034] Preferably, the method for preparing the composite material by vacuum pressure infusion casting in step (3) comprises:

[0035] First, the aluminum alloy is heated to 700±10℃ to melt it;

[0036] Secondly, epoxy resin prepreg and shape memory alloy microwires are alternately laid in the mold;

[0037] Then, the mold was placed in a vacuum pressure infusion casting device and evacuated to -0.1 MPa;

[0038] Again, inject molten aluminum alloy while applying a pressure of 20-30MPa;

[0039] Finally, the pressure was maintained and the mixture was cooled to room temperature at a rate of 10±2°C / min.

[0040] Preferably, the method for heat treating the obtained composite material in step (4) comprises:

[0041] First, the composite material was heated to 530 ± 5 °C at a rate of 5 °C / min and kept at this temperature for 1 h;

[0042] Secondly, water quenching to room temperature;

[0043] Then, aging treatment was performed at 190±5℃ for 4 hours;

[0044] Finally, air cool to room temperature.

[0045] From the perspective of materials science and engineering, the present invention cleverly combines the advantages of metal materials, composite materials and smart materials. The aluminum alloy matrix provides excellent specific strength and specific stiffness, the shape memory alloy microwires give the material intelligent response capabilities, and the microcapsule system realizes the chemical repair function. This multifunctional integration not only overcomes the limitations of a single material system, but also achieves an overall improvement in performance through synergistic effects.

[0046] At the molecular structure and chemical mechanism level, the innovation of this invention is mainly reflected in the following aspects:

[0047] 1. Phase transformation mechanism of shape memory alloy microwires (such as Ni-Ti alloy): Based on molecular orbital theory, the martensitic phase transformation of Ni-Ti alloy involves the coordinated reorganization of atomic arrangement. This reorganization process not only leads to macroscopic shape changes, but also generates significant internal stress. This stress field interacts with the microcapsule system to form a unique "stress induction-chemical repair" synergistic mechanism.

[0048] 2. Chemical reaction of microcapsule repair system: Epoxy resin repair agent (such as DGEBA) forms a cross-linked network through ring-opening polymerization. This process involves the ring opening of epoxy groups and addition reaction with curing agent (such as DDM). From the perspective of molecular orbital theory, this reaction involves the interaction of frontier orbitals to form new covalent bonds, and finally build a three-dimensional network structure with high strength and good toughness.

[0049] 3. Interface interaction: Through carefully designed surface treatment and preparation processes, shape memory alloy microwires and microcapsules form a strong interface bond with the aluminum matrix. This interface not only transmits stress, but also forms a unique "stress buffer zone" on a microscopic scale, which helps to inhibit crack propagation.

[0050] The synergy of these multiple functions brings about a series of unexpected technical effects:

[0051] 1. Intelligent temperature-controlled self-healing: The material can respond spontaneously to temperature changes and achieve a repair process without external intervention. This feature is particularly valuable in environments with large temperature fluctuations.

[0052] 2. Multiple repair capabilities: Thanks to the reversible phase change characteristics of shape memory alloys and the dispersed distribution of microcapsules, the material exhibits excellent cyclic repair capabilities. Experiments show that even after multiple damage-repair cycles, the material can still maintain high repair efficiency.

[0053] 3. Synergistic improvement of mechanical properties: Shape memory alloy microwires not only provide self-repair function, but also significantly improve the overall mechanical properties of the material through the reinforcement effect. Test results show that the tensile strength, elastic modulus and fracture toughness of the material have been significantly improved.

[0054] 4. Excellent environmental adaptability: The material maintains stable performance in a wide temperature range (-20℃ to 80℃) and has excellent corrosion resistance. This feature makes it particularly suitable for long-term service in harsh environments.

[0055] 5. Significantly extended service life: Through the self-repair mechanism, the material can effectively inhibit the expansion of microcracks and significantly extend the service life. Experimental data shows that compared with traditional materials, the service life of the material of the present invention can be extended by more than 200%.

[0056] In summary, the present invention has successfully solved the challenges faced by traditional self-healing materials and high-performance structural materials through innovative material design and preparation methods. This intelligent temperature-controlled self-healing aluminum-based composite material not only achieves a qualitative leap in performance, but also opens up a new research direction in the field of materials science. Its successful development will provide important material support for high-end manufacturing fields such as aerospace and automotive industries, and promote technological progress and innovative development in related industries. In addition, the development of this material also provides new ideas for solving global challenges such as energy and environment, showing broad application prospects. DETAILED DESCRIPTION

[0057] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0058] Example 1

[0059] This embodiment provides an intelligent temperature-controlled self-repairing aluminum-based composite material and a preparation method thereof. The material is composed of the following components in parts by weight: 80 parts of aluminum alloy matrix 6061-T6, 5 parts of nickel-titanium alloy microwires, and 15 parts of epoxy resin prepreg containing microcapsules (including 3 parts of epoxy resin, 0.3 parts of curing agent, and 1 part of microcapsules).

[0060] The preparation method of the material comprises the following steps:

[0061] (1) Preparation of microcapsules: First, add 200 mL of deionized water to a 500 mL three-necked flask and set the stirring speed to 400 rpm. Then add 2 g of polyvinyl alcohol (PVA, 87% hydrolyzed, average molecular weight 13,000) and 0.5 g of sodium dodecylbenzene sulfonate (SDBS) as emulsifier and co-emulsifier. Raise the temperature to 38 ° C and stir until completely dissolved. Next, mix 50 g of dicyclopentadiene (DCPD) with 0.5 g of Grubbs first-generation catalyst, slowly add it to the PVA solution, increase the stirring speed to 800 rpm, and emulsify for 10 minutes. Then add 5 g of urea and 0.5 g of ammonium chloride and continue stirring for 5 minutes. Slowly add 13 mL of 37% formaldehyde solution, raise the temperature to 53 ° C, and keep it for 4 hours. Finally, cool naturally to room temperature, filter, wash 3 times with deionized water, and vacuum dry at 38 ° C for 24 hours.

[0062] (2) Preparation of epoxy resin prepreg containing microcapsules: First, add 100g of bisphenol A epoxy resin (DGEBA) epoxy resin in a 250mL beaker. Then add 10g of 4,4'-diaminodiphenylmethane (DDM) curing agent and stir at 58°C for 30 minutes until completely dissolved. Then add 15g of the prepared microcapsules and stir gently at 38°C for 10 minutes to avoid destroying the microcapsules. The mixture is coated on glass fiber cloth to make a prepreg. Finally, vacuum dry at room temperature for 12 hours.

[0063] (3) Prepare the composite material by vacuum pressure infusion casting: First, heat the 6061-T6 aluminum alloy to 690°C to melt it. Then evenly lay a layer of epoxy resin prepreg on the bottom of the mold, and evenly distribute nickel-titanium alloy microwires (50 μm in diameter) on the prepreg. Repeat this step until the desired thickness is reached. Place the mold in a vacuum pressure infusion casting equipment, evacuate to -0.1 MPa, and hold for 10 minutes. Inject the molten aluminum alloy while applying a pressure of 20 MPa. Maintain the pressure and cool to room temperature at a rate of 8°C / min.

[0064] (4) Heat treatment: The composite material was heated to 525°C at a rate of 5°C / min and kept at that temperature for 1 hour. It was then water quenched to room temperature, aged at 185°C for 4 hours, and finally air-cooled to room temperature.

[0065] Preferably, in the embodiment of the present invention, the shape memory effect of the nickel-titanium alloy microwire can generate stress when the temperature changes, induce the microcapsule to rupture and release the repair agent. At the same time, this stress can also promote crack closure, forming a synergistic repair effect with the epoxy resin repair agent. This dual action mechanism significantly improves the self-repair ability of the material, enabling it to quickly restore performance after damage.

[0066] Example 2

[0067] This embodiment provides another intelligent temperature-controlled self-repairing aluminum-based composite material and its preparation method. The material is composed of the following components by weight: 5 parts of aluminum alloy matrix 6061-T68, 10 parts of nickel-titanium alloy microwires, and 5 parts of epoxy resin prepreg containing microcapsules (including 5.5 parts of epoxy resin, 0.55 parts of curing agent, and 2 parts of microcapsules).

[0068] The preparation method of the material comprises the following steps:

[0069] (1) Preparation of microcapsules: First, add 200 mL of deionized water to a 500 mL three-necked flask and set the stirring speed to 400 rpm. Then add 2 g of polyvinyl alcohol (PVA, 88% hydrolyzed, average molecular weight 18,000) and 0.5 g of sodium dodecylbenzene sulfonate (SDBS). Raise the temperature to 40°C and stir until completely dissolved. Next, mix 50 g of dicyclopentadiene (DCPD) with 0.5 g of Grubbs first-generation catalyst, slowly add it to the PVA solution, increase the stirring speed to 800 rpm, and emulsify for 10 minutes. Then add 5 g of urea and 0.5 g of ammonium chloride and continue stirring for 5 minutes. Slowly add 13 mL of 37% formaldehyde solution, raise the temperature to 55°C, and keep it for 4 hours. Finally, cool naturally to room temperature, filter, wash 3 times with deionized water, and vacuum dry at 40°C for 24 hours.

[0070] (2) Preparation of epoxy resin prepreg containing microcapsules: First, add 100g of bisphenol A epoxy resin (DGEBA) epoxy resin in a 250mL beaker. Then add 10g of 4,4'-diaminodiphenylmethane (DDM) curing agent and stir at 60°C for 30 minutes until completely dissolved. Then add 15g of the prepared microcapsules and stir gently at 40°C for 10 minutes. The mixture is coated on glass fiber cloth to make a prepreg. Finally, vacuum dry at room temperature for 12 hours.

[0071] (3) Prepare the composite material by vacuum pressure infusion casting: First, heat the 6061-T6 aluminum alloy to 700°C to melt it. Then evenly lay a layer of epoxy resin prepreg on the bottom of the mold, and evenly distribute nickel-titanium alloy microwires (75 μm in diameter) on the prepreg. Repeat this step until the desired thickness is reached. Place the mold in a vacuum pressure infusion casting equipment, evacuate to -0.1 MPa, and hold for 10 minutes. Inject the molten aluminum alloy while applying a pressure of 25 MPa. Maintain the pressure and cool to room temperature at a rate of 10°C / min.

[0072] (4) Heat treatment: The composite material was heated to 530°C at a rate of 5°C / min and kept at that temperature for 1 hour. It was then quenched in water to room temperature, aged at 190°C for 4 hours, and finally air-cooled to room temperature.

[0073] Preferably, in the embodiment of the present invention, increasing the content of nickel-titanium alloy microwires can improve the shape memory effect and superelasticity of the material, thereby enhancing its self-repairing ability. At the same time, increasing the ratio of epoxy resin and curing agent can enhance the bonding strength of the repair agent and further improve the repair effect.

[0074] Example 3

[0075] This embodiment provides a third intelligent temperature-controlled self-repairing aluminum-based composite material and a preparation method thereof. The material is composed of the following components in parts by weight: 90 parts of aluminum alloy matrix 6061-T6, 15 parts of nickel-titanium alloy microwires, and 11.8 parts of epoxy resin prepreg containing microcapsules (including 8 parts of epoxy resin, 0.8 parts of curing agent, and 3 parts of microcapsules).

[0076] The preparation method of the material comprises the following steps:

[0077] (1) Preparation of microcapsules: First, add 200 mL of deionized water to a 500 mL three-necked flask and set the stirring speed to 400 rpm. Then add 2 g of polyvinyl alcohol (PVA, 89% hydrolyzed, average molecular weight 23,000) and 0.5 g of sodium dodecylbenzene sulfonate (SDBS). Raise the temperature to 42 ° C and stir until completely dissolved. Next, mix 50 g of dicyclopentadiene (DCPD) with 0.5 g of Grubbs first-generation catalyst, slowly add it to the PVA solution, increase the stirring speed to 800 rpm, and emulsify for 10 minutes. Then add 5 g of urea and 0.5 g of ammonium chloride and continue stirring for 5 minutes. Slowly add 13 mL of 37% formaldehyde solution, raise the temperature to 57 ° C, and keep it for 4 hours. Finally, cool naturally to room temperature, filter, wash 3 times with deionized water, and vacuum dry at 42 ° C for 24 hours.

[0078] (2) Preparation of epoxy resin prepreg containing microcapsules: First, add 100g of bisphenol A epoxy resin (DGEBA) epoxy resin into a 250mL beaker. Then add 10g of 4,4'-diaminodiphenylmethane (DDM) curing agent and stir at 62°C for 30 minutes until completely dissolved. Then add 15g of the prepared microcapsules and stir gently at 42°C for 10 minutes. The mixture is coated on glass fiber cloth to make a prepreg. Finally, vacuum dry at room temperature for 12 hours.

[0079] (3) Prepare the composite material by vacuum pressure infusion casting: First, heat the 6061-T6 aluminum alloy to 710°C to melt it. Then evenly lay a layer of epoxy resin prepreg on the bottom of the mold, and evenly distribute nickel-titanium alloy microwires (100 μm in diameter) on the prepreg. Repeat this step until the desired thickness is reached. Place the mold in a vacuum pressure infusion casting equipment, evacuate to -0.1 MPa, and hold for 10 minutes. Inject the molten aluminum alloy while applying a pressure of 30 MPa. Maintain the pressure and cool to room temperature at a rate of 12°C / min.

[0080] (4) Heat treatment: The composite material was heated to 535°C at a rate of 5°C / min and kept at that temperature for 1 hour. It was then quenched in water to room temperature, aged at 195°C for 4 hours, and finally air-cooled to room temperature.

[0081] Preferably, in the embodiment of the present invention, further increasing the content and diameter of nickel-titanium alloy microwires can significantly improve the shape memory effect and superelasticity of the material, thereby greatly enhancing its self-repairing ability. At the same time, increasing the content of microcapsules can increase the reserve of the repair agent, so that the material has a more durable self-repairing ability.

[0082] Example 4

[0083] This embodiment provides a fourth intelligent temperature-controlled self-repairing aluminum-based composite material and a preparation method thereof. The material is composed of the following components by weight: 7.5 parts of aluminum alloy matrix 6061-T68, 7.5 parts of nickel-titanium alloy microwires, and 8.05 parts of epoxy resin prepreg containing microcapsules (including 5.75 parts of epoxy resin, 0.575 parts of curing agent, and 1.725 parts of microcapsules).

[0084] The preparation method of the material comprises the following steps:

[0085] (1) Preparation of microcapsules: First, add 200 mL of deionized water to a 500 mL three-necked flask and set the stirring speed to 400 rpm. Then add 2 g of polyvinyl alcohol (PVA, 88.5% hydrolyzed, average molecular weight 20,500) and 0.5 g of sodium dodecylbenzene sulfonate (SDBS). Raise the temperature to 41 °C and stir until completely dissolved. Next, mix 50 g of dicyclopentadiene (DCPD) with 0.5 g of Grubbs first-generation catalyst, slowly add it to the PVA solution, increase the stirring speed to 800 rpm, and emulsify for 10 minutes. Then add 5 g of urea and 0.5 g of ammonium chloride and continue stirring for 5 minutes. Slowly add 13 mL of 37% formaldehyde solution, raise the temperature to 56 °C, and maintain for 4 hours. Finally, cool naturally to room temperature, filter, wash 3 times with deionized water, and vacuum dry at 41 °C for 24 hours.

[0086] (2) Preparation of epoxy resin prepreg containing microcapsules: First, add 100g of bisphenol A epoxy resin (DGEBA) epoxy resin in a 250mL beaker. Then add 10g of 4,4'-diaminodiphenylmethane (DDM) curing agent and stir at 61°C for 30 minutes until completely dissolved. Then add 15g of the prepared microcapsules and stir gently at 41°C for 10 minutes. The mixture is coated on glass fiber cloth to make a prepreg. Finally, vacuum dry at room temperature for 12 hours.

[0087] (3) Prepare the composite material by vacuum pressure infusion casting: First, heat the 6061-T6 aluminum alloy to 705°C to melt it. Then evenly lay a layer of epoxy resin prepreg on the bottom of the mold, and evenly distribute nickel-titanium alloy microwires (diameter 87.5 μm) on the prepreg. Repeat this step until the desired thickness is reached. Place the mold in a vacuum pressure infusion casting equipment, evacuate to -0.1 MPa, and hold for 10 minutes. Inject the molten aluminum alloy while applying a pressure of 27.5 MPa. Maintain the pressure and cool to room temperature at a rate of 11°C / min.

[0088] (4) Heat treatment: The composite material was heated to 532.5°C at a rate of 5°C / min and kept at that temperature for 1 hour. Then, it was water quenched to room temperature, aged at 192.5°C for 4 hours, and finally air-cooled to room temperature.

[0089] Preferably, in the embodiment of the present invention, the selection of such component ratio and preparation parameters is intended to achieve a balance of various properties. The moderate content of nickel-titanium alloy microwires can provide sufficient shape memory effect and superelasticity without excessively affecting the lightweight characteristics of the aluminum matrix. At the same time, the proportion of epoxy resin prepreg is also optimized to ensure sufficient repair agent reserves and good interface bonding strength.

[0090] Through the above four embodiments, it can be seen that the intelligent temperature-controlled self-repairing aluminum-based composite material of the present invention exhibits excellent performance and flexibility. This material combines the light weight and high strength characteristics of aluminum alloy, the intelligent response ability of shape memory alloy and the self-repairing function of microcapsule repair system to form a unique multifunctional composite material.

[0091] In all embodiments, the stress generated by the nickel-titanium alloy microwires during temperature changes can not only induce the microcapsule to rupture and release the repair agent, but also promote crack closure. This dual action mechanism significantly improves the self-repair efficiency of the material. At the same time, by adjusting the proportion of each component and the preparation parameters, the material performance can be optimized according to the needs of different application scenarios.

[0092] It is worth noting that the preparation process of microcapsules is crucial to the performance of the entire material system. By precisely controlling the reaction temperature, time, and stirring speed, microcapsules with uniform size and appropriate wall thickness can be obtained, which directly affects the storage and release effects of the repair agent. Similarly, the preparation of epoxy resin prepregs also requires precise control to ensure that the microcapsules are evenly dispersed and not destroyed.

[0093] The application of vacuum pressure infusion casting solves the problem of poor interface bonding in the preparation of traditional composite materials. By vacuuming and applying pressure, it can ensure that the molten aluminum alloy fully infiltrates the prepreg and shape memory alloy microwires, thereby forming a strong interface bond. This not only improves the overall mechanical properties of the material, but also provides a good foundation for the self-healing function.

[0094] Finally, precise control of the heat treatment process is essential to achieve the best performance of the material. The choice of solution treatment temperature and aging treatment parameters directly affects the strength and toughness of the aluminum alloy matrix, and also affects the phase transformation characteristics of the shape memory alloy microwires.

[0095] In summary, this intelligent temperature-controlled self-healing aluminum-based composite material achieves multifunctional integration and performance optimization through ingenious material design and precise preparation process. It not only has excellent mechanical properties and lightweight characteristics, but also has intelligent response and self-healing capabilities, providing a new type of high-performance material choice for high-end manufacturing fields such as aerospace and automotive industries.

[0096] Comparative Example 1:

[0097] This comparative example provides an aluminum-based composite material without shape memory alloy microwires and a preparation method thereof. The material is composed of the following components by weight: 5 parts of aluminum alloy matrix 6061-T68, 15 parts of epoxy resin prepreg containing microcapsules (including 3 parts of epoxy resin, 0.3 parts of curing agent, and 1 part of microcapsules).

[0098] The preparation method of the material is basically the same as that of Example 1, but the addition of nickel-titanium alloy microwires is omitted in step (3). The other steps and parameters remain unchanged.

[0099] Preferably, in this comparative example, due to the lack of shape memory alloy microwires, the material loses its temperature responsiveness and the ability to induce microcapsule rupture by stress. This results in the self-repairing process relying solely on the destruction of microcapsules by external stress, greatly reducing the repair efficiency. At the same time, the crack closure ability is also significantly reduced, affecting the effective filling of the repair agent.

[0100] Comparative Example 2:

[0101] This comparative example provides a smart aluminum-based composite material without microcapsules and a preparation method thereof. The material is composed of the following components in parts by weight: 90 parts of aluminum alloy matrix 6061-T6 and 10 parts of nickel-titanium alloy microwires.

[0102] The preparation method of the material is based on Example 2, but the preparation of microcapsules and epoxy resin prepreg in steps (1) and (2) is omitted. In step (3), nickel-titanium alloy microwires are directly added to the aluminum alloy melt, and other parameters remain unchanged.

[0103] Preferably, in this comparative example, although the material retains the shape memory effect and superelasticity, it lacks the storage and release mechanism of the repair agent. This results in the material being unable to be effectively chemically repaired after being damaged, and only relying on the shape memory effect for physical closure, which greatly limits the self-repairing ability.

[0104] Comparative Example 3:

[0105] This comparative example provides an intelligent temperature-controlled self-repairing aluminum-based composite material using a traditional curing agent and a preparation method thereof. The material components are the same as those in Example 3, but the DDM curing agent is replaced by an equal amount of diethylenetriamine (DETA).

[0106] The preparation method is basically the same as that of Example 3, except that DETA is used instead of DDM in step (2). The other steps and parameters remain unchanged.

[0107] Preferably, in this comparative example, DETA is used as an aliphatic amine curing agent, and its curing speed is faster, but its heat resistance and mechanical properties are slightly lower than those of DDM. This may lead to a decrease in the high temperature performance of the epoxy resin matrix, affecting the self-healing effect of the material at higher temperatures. At the same time, due to the difference in molecular structure, the interfacial bonding strength between the epoxy resin cured by DETA and the aluminum matrix may not be as good as that of the DDM system, which may affect the overall mechanical properties and repair effect of the material.

[0108] Comparative Example 4:

[0109] This comparative example provides an intelligent temperature-controlled self-repairing aluminum-based composite material using different microcapsule wall materials and a preparation method thereof. The material components are the same as those in Example 4, but the wall material of the microcapsule is changed from polyurea formaldehyde to polystyrene.

[0110] The preparation method is basically the same as that of Example 4, but in step (1), the polystyrene microcapsules are prepared by suspension polymerization. Specifically, 50 g of styrene monomer, 0.5 g of initiator azobisisobutyronitrile (AIBN) and 50 g of DCPD are mixed, added to an aqueous solution containing 2% polyvinyl alcohol, and stirred at 70° C. for 4 hours. The other steps and parameters remain unchanged.

[0111] Preferably, in this comparative example, although polystyrene microcapsules have good chemical stability, their wall material strength and thermal stability are not as good as those of polyurea formaldehyde. This may cause the microcapsules to break more easily during the preparation of the composite material, reducing the effective storage amount of the repair agent. At the same time, the glass transition temperature of polystyrene is relatively low, which may affect the self-healing performance of the material at higher temperatures.

[0112] Comparative Example 5:

[0113] This comparative example provides an intelligent temperature-controlled self-repairing aluminum-based composite material without heat treatment and a preparation method thereof. The material components are the same as those in Example 1, but the final heat treatment step is omitted.

[0114] The preparation method is basically the same as that of Example 1, except that the heat treatment process in step (4) is omitted. The other steps and parameters remain unchanged.

[0115] Preferably, in this comparative example, due to the lack of heat treatment process, the strength and toughness of the aluminum alloy matrix cannot reach the optimal state. At the same time, the phase change characteristics of the shape memory alloy microwires may also be affected, resulting in reduced temperature responsiveness and superelasticity. This not only affects the overall mechanical properties of the material, but also may reduce the effects of stress induction and crack closure during the self-repair process.

[0116] Comparative Example 6:

[0117] This comparative example provides an intelligent temperature-controlled self-repairing composite material using different aluminum alloy matrices and a preparation method thereof. The material composition is the same as that of Example 2, but the 6061-T6 aluminum alloy is replaced by the 7075-T6 aluminum alloy.

[0118] The preparation method is basically the same as that of Example 2, but in all steps involving aluminum alloy, 7075-T6 is used instead of 6061-T6. Other steps and parameters remain unchanged.

[0119] Preferably, in this comparative example, although the 7075-T6 aluminum alloy has higher strength, its ductility and corrosion resistance are not as good as 6061-T6. This may lead to a decrease in the plastic deformation ability of the composite material during the self-repair process, affecting the crack closure effect. At the same time, since the 7075 alloy contains more zinc and copper elements, it may produce a stronger interface reaction with the shape memory alloy microwire, affecting the phase change characteristics and long-term stability of the microwire.

[0120] Through the above six comparative examples, the present invention can clearly see the superiority of the intelligent temperature-controlled self-healing aluminum-based composite material of the present invention. Comparative Examples 1 and 2 respectively verify the necessity of shape memory alloy microwires and microcapsule repair systems, highlighting the importance of the synergistic effect of the two. Comparative Examples 3 and 4 demonstrate the influence of the selection of curing agent and microcapsule wall material on material properties, verifying the optimal design of the present invention in these aspects. Comparative Example 5 emphasizes the key role of heat treatment process on the overall performance of the material, while Comparative Example 6 demonstrates the influence of the selection of aluminum alloy matrix on the self-healing effect.

[0121] Through these comparisons, the present invention can be concluded that the present invention achieves the best synergy of shape memory effect, microcapsule repair system and aluminum matrix performance through carefully designed material composition and preparation process, thereby obtaining excellent intelligent temperature control self-repairing ability and overall performance. The realization of this multifunctional integration and synergistic effect reflects the creativity and technological advancement of the present invention.

[0122] Based on the characteristics of the intelligent temperature-controlled self-healing aluminum-based composite material and its preparation method, the present invention designed a series of test experiments to comprehensively evaluate the performance and self-healing ability of the material. These tests not only cover the basic mechanical properties of the material, but also pay special attention to its intelligent temperature-controlled self-healing characteristics.

[0123] First, the present invention conducts basic mechanical property tests on the material, including tensile strength, elastic modulus and fracture toughness. These tests are conducted using standard material mechanical testing methods and a universal material testing machine. The test conditions are room temperature (25±2°C), relative humidity 50±5%, and a tensile rate of 2mm / min.

[0124] Secondly, in order to evaluate the self-healing ability of the material, the present invention designed an innovative cyclic damage-repair test. In this test, the present invention first prefabricated a crack with a length of 10mm and a width of 0.5mm at the center of the specimen. Then, the present invention placed the specimen in a constant temperature and humidity chamber to simulate different environmental conditions. The present invention selected three temperature points: 25°C (room temperature), 45°C (slightly heated) and 65°C (significantly heated). At each temperature, the present invention performed 5 cycles of damage-repair process. Each cycle includes the following steps:

[0125] 1. Apply tension to the specimen to extend the crack by 1 mm.

[0126] 2. Unload and keep at the specified temperature for 24 hours to allow the material to self-heal.

[0127] 3. Measure crack length and residual strength of the material.

[0128] In addition, the present invention also conducted a thermomechanical cycle test to evaluate the responsiveness and stability of the material under temperature changes. The test temperature range was -20°C to 80°C, the heating and cooling rate was 2°C / min, and a total of 100 cycles were performed.

[0129] Finally, the present invention also conducted a corrosion resistance test, where the sample was immersed in a 3.5% NaCl solution for 30 days, and the weight loss and surface morphology change of the material were measured every 5 days.

[0130] The following are the detailed test results of all embodiments and comparative examples:

[0131] Table 1: Basic mechanical properties and self-healing ability test results

[0132]

[0133] Table 2: Thermomechanical cycle test and corrosion resistance test results

[0134]

[0135] According to the above test results, Example 3 exhibits the best comprehensive performance and can be regarded as the best embodiment of the present invention. It not only has excellent mechanical properties, but also exhibits excellent self-repairing ability and environmental stability.

[0136] After in-depth analysis of these test data, the present invention can be found to have the following unexpected technical effects:

[0137] 1. Temperature-sensitive self-repairing ability: As the temperature rises, the self-repairing efficiency increases significantly. This temperature-responsive self-repairing effect far exceeds that of traditional self-repairing materials. This is because the stress generated by the shape memory alloy microwires when the temperature changes can not only induce the microcapsule to rupture and release the repair agent, but also promote the closure of the cracks, forming a synergistic self-repairing mechanism.

[0138] 2. Excellent cyclic self-repair ability: After multiple damage-repair cycles, the material can still maintain a high repair efficiency. This shows that the self-repair system of the present invention is durable and repeatable, which is of great significance for extending the service life of the material.

[0139] 3. Excellent thermomechanical stability: After 100 thermal cycles, the material strength retention rate is as high as 96% (Example 3). This shows that the material of the present invention can still maintain excellent performance under repeated temperature changes, which is a major breakthrough for materials used in environments with large temperature fluctuations.

[0140] 4. Significantly improved corrosion resistance: Compared with traditional aluminum alloys, the material of the present invention exhibits better corrosion resistance. This may be due to the synergistic effect of shape memory alloy microwires and epoxy resin prepreg to form a protective network structure.

[0141] 5. Synergistic improvement of comprehensive performance: The present invention not only has a significant improvement in self-repairing ability, but also has enhanced basic mechanical properties. This shows that the shape memory alloy microwire and microcapsule system not only does not weaken the performance of the aluminum matrix, but enhances the overall performance of the material through synergistic effects.

[0142] These unexpected technical effects fully demonstrate the innovation and superiority of the present invention. By cleverly combining shape memory alloys, microcapsule technology and aluminum-based composite materials, the present invention realizes a new type of material with intelligent temperature control self-repairing ability, excellent mechanical properties and environmental stability. This material has broad application prospects in fields such as aerospace and automotive industries that require long-life, high-reliability materials.

[0143] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. Intelligent temperature-controlled self-repairing aluminum-based composite material, characterized in that: The material comprises the following components in parts by weight: Aluminum alloy matrix 80-90 parts; 5-15 parts of shape memory alloy microwires; 4.3-11.8 parts of epoxy resin prepreg containing microcapsules; Wherein, the epoxy resin prepreg containing microcapsules is composed of the following components: Epoxy resin 3-8 parts; Curing agent 0.3-0.8 parts; 1-3 parts of microcapsules.

2. The intelligent temperature-controlled self-repairing aluminum-based composite material according to claim 1, characterized in that: The aluminum alloy substrate is 6061-T6 aluminum alloy.

3. The intelligent temperature-controlled self-repairing aluminum-based composite material according to claim 1, characterized in that: The shape memory alloy microwire is nickel-titanium alloy, and its diameter is 50-100 μm.

4. The intelligent temperature-controlled self-repairing aluminum-based composite material according to claim 1, characterized in that: The epoxy resin is bisphenol A epoxy resin, and the curing agent is 4,4'-diaminodiphenylmethane.

5. The intelligent temperature-controlled self-repairing aluminum-based composite material according to claim 1, characterized in that: The shell material of the microcapsule is polyurea formaldehyde, and the core material is dicyclopentadiene.

6. The method for preparing the intelligent temperature-controlled self-repairing aluminum-based composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) preparing microcapsules; (2) preparing epoxy resin prepreg containing microcapsules; (3) preparing composite materials by vacuum pressure infusion casting; (4) Heat treating the obtained composite material.

7. The preparation method according to claim 6, characterized in that: The method for preparing microcapsules in step (1) comprises: First, add deionized water, polyvinyl alcohol and sodium dodecylbenzene sulfonate into a three-necked flask, heat to 40±2℃ and stir to dissolve; Secondly, a mixture of dicyclopentadiene and Grubbs first generation catalyst is added to the above solution for emulsification; Then, urea and ammonium chloride were added, and formaldehyde solution was added dropwise; Again, the temperature was raised to 55 ± 2 °C and maintained for 4 hours; Finally, it was cooled, filtered, washed, and vacuum dried at 40±2°C for 24 hours.

8. The preparation method according to claim 6, characterized in that: The method for preparing the epoxy resin prepreg containing microcapsules in step (2) comprises: First, the epoxy resin and curing agent were stirred and mixed at 60±2℃; Secondly, add microcapsules and stir gently at 40±2℃; Then, the mixture was applied to a fiberglass cloth; Finally, vacuum drying was performed at room temperature for 12 h.

9. The preparation method according to claim 6, characterized in that: The method for preparing the composite material by vacuum pressure infusion casting in step (3) comprises: First, the aluminum alloy is heated to 700±10℃ to melt it; Secondly, epoxy resin prepreg and shape memory alloy microwires are alternately laid in the mold; Then, the mold was placed in a vacuum pressure infusion casting device and evacuated to -0.1 MPa; Again, inject molten aluminum alloy while applying a pressure of 20-30MPa; Finally, the pressure was maintained and the mixture was cooled to room temperature at a rate of 10±2°C / min.

10. The preparation method according to claim 6, characterized in that: The method of heat treating the obtained composite material in step (4) comprises: First, the composite material was heated to 530 ± 5 °C at a rate of 5 °C / min and kept at this temperature for 1 h; Secondly, water quenching to room temperature; Then, aging treatment was performed at 190±5℃ for 4 hours; Finally, air cool to room temperature.

Citation Information

Cited By

  • High-entropy alloy microwire and preparation method thereof

    CN120210689A

  • Reusable fire barrier and preparation method thereof

    CN120698770A